2009
DOI: 10.1159/000209860
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cerebral S100B Protein Is Associated with Depressive Symptoms following Myocardial Infarction

Abstract: Background: Prevalence of depressive symptoms in the post-myocardial infarction (MI) period varies from 8 to 30%. Cerebral damage after MI, caused by transient ischemia, an inflammatory response or both, may contribute to development of post-MI depression. S100B is an established protein marker of cerebral damage. In a pilot study, the authors assessed whether S100B serum levels are: (1) increased during the week after MI, and (2) related to depressive symptoms during index hospital admission and the year foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
(86 reference statements)
0
6
0
1
Order By: Relevance
“…They demonstrated that a single dose of recombinant sTNF-R1 was accompanied by initial inhibition of both BBB permeability and CNS inflammation leading to diminishing of disease symptoms for 5 days. This mechanism might be relevant as in a previous study we demonstrated an increased permeability of the BBB during the first week after MI [42] , which might have long-lasting effects on the upregulated transport of TNF-␣ [38] .…”
Section: Discussionmentioning
confidence: 57%
“…They demonstrated that a single dose of recombinant sTNF-R1 was accompanied by initial inhibition of both BBB permeability and CNS inflammation leading to diminishing of disease symptoms for 5 days. This mechanism might be relevant as in a previous study we demonstrated an increased permeability of the BBB during the first week after MI [42] , which might have long-lasting effects on the upregulated transport of TNF-␣ [38] .…”
Section: Discussionmentioning
confidence: 57%
“…When it is present in nanomolar concentrations, S100B acts as a growth and differentiation factor for neurons and astrocytes. When it is present in micromolar concentrations, S100B exerts neurotoxic activity and induces the apoptosis of neurons and astrocytes [28] .The results of this study indicate that serum S100B levels are down regulated in GAD patients compared to healthy controls. Limited researches have reported controversial results of S100B on anxiety, Bergh C D [29] reported patients with elevated S100B suffered more anxiety 3-6 years after cardiac surgery.…”
Section: Discussionmentioning
confidence: 63%
“…In a healthy state, the low S100B protein level in brain is maintained. 56 At lower (nM) concentration, it exerts neuroprotective effect by promoting neuronal survival and neuritic outgrowth but at higher concentration (μM) it participates in a cascade of events leading to neuronal degeneration. 57,58 In several neuropathological conditions, a 10-60-fold increase in serum S100B…”
Section: Discussionmentioning
confidence: 99%